Genetic CYP2A6 Polymorphism May Worsen Glycohemoglobin Levels: Study among Javanese Indonesian Smokers - Patramurti, Christine; Virginia, Dita Maria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
We have examined the inactive CYP2A6 alleles gene, including CYP2A6*4, CYP2A6*7, and CYP2A6*9, associated with glycohemoglobin levels among Javanese Indonesian smokers. There are 106 smokers participating in this study. Due to the number of cigarettes smoked per day, there are three groups of smokers: light, intermediate, and heavy smokers, with 98.7% being light and intermediated smokers while the rest are heavy smokers. All participants had smoked for more than 10 years, indicating they had been exposed to nicotine for a long time. Based on their genotype, there were four groups of smokers, including fast, intermediate, slow, and poor metabolizers. Most fast and intermediate metabolizers have HbA1c levels in the normal range (<5.7). On the other hand, most slow metabolizers have Hb1c levels >5.7, and all fast metabolizers have HbA1c levels >5.7, indicating that they the prediabetes and diabetes. The chi-square test showed a relationship between CYP2A6 polymorphism and HbA1c levels among the participants (P-value 0.000 <0.005 and χ2=54.6, df=1). The presence of an inactive allele will worsen the HbA1c levels in smokers.